ANALISA POTENSI EROSI DI SUB DAS (DAERAH ALIRAN SUNGAI) KOBE KECAMATAN WEDA TENGAH KABUPATEN HALMAHERA TENGAH - Zulkarnain K Misbah; Muhammad Taufiq Yudha Saputra (Journal of Science and Engineering, 2026)
The Kobe Sub Watershed is the closest river to the nickel mining area, thus affecting the characteristics of the Sub Watershed. The Kobe Sub Watershed (Watershed) is also a source of water for the daily needs of the people in Kobe Village and its surroundings. The decline of natural resources is inevitable, especially land and water resources, including the condition of the Sub-Watershed. The purpose of this study is to determine the runoff discharge value in each area reviewed in the Kobe Sub Watershed, to find out and classify the annual erosion potential in the Kobe Sub Watershed and to determine the percentage of land criticality in the Kobe Sub Watershed. The method of analysis of erosion potential uses the USLE Modification method based on the Geographic Information System (ArcGis). After calculating the erosion rate in the Kobe Sub Watershed in 4 zones with the USLE Modification method, different results were obtained. Zone I with a potential erosion rate of 7,800,332 tons/ha/year, zone II with an erosion rate of 6,901,822 tons/ha/year, zone III with an erosion rate of 6,912.75 tons/ha/year, zone IV 6,893,576 tons/ha/year. 3. The level of erosion hazard in the Kobe Sub Watershed is said to be severe, the rate of erosion is said to be severe because it causes land to become critical, and the percentage of erosion hazard level ranges from Very Heavy with a percentage of 3%, Heavy 21%, Medium 47% and Light 29%. With land criticality in the Kobe Sub-Watershed which is divided into four, namely Critical Potential with a percentage of 29%, semi-critical with a percentage of 47%, critical with a percentage of 21%, and very critical with a percentage of 3%.